1999
DOI: 10.1095/biolreprod60.1.78
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of Ovarian Inhibin and Its Physiologic Roles in the Regulation of Follicle-Stimulating Hormone Secretion during the Estrous Cycle of the Female Guinea Pig1

Abstract: To characterize inhibin secretion during the estrous cycle in guinea pigs, the concentrations of plasma inhibin, estradiol, progesterone, and FSH were determined. A significant positive correlation was observed between inhibin and estradiol throughout the estrous cycle. Plasma inhibin and estradiol started to increase a few days before ovulation (Day 0 = day of estimated ovulation), and decreased after ovulation. These two hormones remained low during the luteal phase. The immunoreactivity of inhibin alpha, be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 49 publications
5
35
0
1
Order By: Relevance
“…Estradiol concentrations in the granulosa cell conditioned medium were determined by RIA [16,17]. The intra-coefficients of variation for estradiol determination in this laboratory were less than 9%.…”
Section: Radioimmunoassays (Ria) Of Estradiol Cgmp and Campmentioning
confidence: 97%
“…Estradiol concentrations in the granulosa cell conditioned medium were determined by RIA [16,17]. The intra-coefficients of variation for estradiol determination in this laboratory were less than 9%.…”
Section: Radioimmunoassays (Ria) Of Estradiol Cgmp and Campmentioning
confidence: 97%
“…In vivo efficiency of the antiserum was ensured by an increase in plasma concentration of FSH after an i.v. injection of the antiserum, and described previously [29].…”
Section: Animals and Implantation Of Progesterone-containing Capsulesmentioning
confidence: 99%
“…Passive immunization against inhibin can increase the secretion of FSH in female guinea pigs [29] as well as in the other animals [14,16,17,21,26]. However, the mechanism that regulates the onset and completion of the compensatory response to hemiovariectomy remains obscure in guinea pigs.…”
mentioning
confidence: 99%
“…An in vitro assay indicated that cells of LUFs were more sensitive to hCG (Westfahl, 1993). The possible reason for this might be that the high dose of eCG can destroy or inhibit granulosa cells, which secrete inhibins to regulate the function of FSH (Shi et al, 1999;Ozawa et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Guinea pigs are a more reliable reproductive model as compared with mice or rats (Silva et al, 1998;Shi et al, 1999;Kulduk et al, 2014;Sun et al, 2014), because they share similarities with humans and large domestic animals in estrous cycles and prolonged pregnancy (van Kan et al, 2009). Guinea pigs, only ovulate a few oocytes (3.6±0.1) in one typical estrous cycle (Suzuki et al, 1993), and the majority of follicles are lost by atresia (Hermreck and Greenwald, 1964) in the four continuous stages (Wang et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%